Mediastinal lymph node enlargement in idiopathic pulmonary fibrosis: relationships with disease progression and pulmonary function trends - Giacomo Sgalla; Anna Rita Larici; Nicoletta Golfi; Mariarosaria Calvello; Alessandra Farchione; Annemilia Del Ciello; Francesco Varone; Bruno Iovene; Riccardo Manfredi; Luca Richeldi (BMC Pulmonary Medicine, 2020)
Abstract Background and objectives Evidence of mediastinal Lymph Node Enlargement (LNE) on CT scan is a common finding in idiopathic pulmonary fibrosis (IPF). We sought to investigate whether the involvement of mediastinal lymph nodes is associated with accelerated disease progression, and explored the changes occurring in mediastinal lymph nodes during the radiological follow up of these patients. Methods This retrospective study included IPF patients referred to a single ILD centre in Italy. A consensus-based assessment of mediastinal LNE on chest CT scan was performed by two thoracic radiologists. Kaplan-Meier curves and multivariate Cox proportional hazards regression were used to assess hazard ratios for mortality and disease progression (defined as categorical FVC decline ≥10%). The annualized rates of change in functional parameters for each patient were calculated using mixed linear models. Results The study population consisted of 152 IPF patients, of whom 135 (89%) received antifibrotic treatment for IPF during the study follow up. Patients having evidence of 3 or more enlarged mediastinal lymph nodes on baseline CT scan showed increased rates of mortality (HR 5.03, 95% CI 1.86–13.62, p ≤ 0.001) and significant disease progression (HR 2.99, 95% CI 1.22–7.33, p = 0.17) as compared to patients without LNE, after adjusting for GAP stage. Among 62 patients with LNE who underwent a follow up CT scan of the chest and received antifibrotic treatment, 57 (92%) maintained evidence mediastinal LNE over time. Conclusions Diffuse mediastinal lymph node involvement predicts clinically meaningful functional deterioration in patients with IPF.